Clinical Impact and Predictors of Troponin Elevation in Patients With COVID-19 - Case, Brian C. (Cardiovasc Revasc Med, 2021)
BACKGROUND: Cardiac involvement in coronavirus disease 2019 (COVID-19) is known, manifested by troponin elevation. Studies in the initial phase of the pandemic demonstrated that these patients tended to have a worse prognosis than patients without myocardial injury. We sought to evaluate the clinical impact of significant troponin elevation in COVID-19-positive patients, along with predictors of poor outcomes, over the span of the pandemic to date. METHODS: We analyzed COVID-19-positive patients who presented to the MedStar Health system (11 hospitals in Washington, DC, and Maryland) during the pandemic (March 1–June 30, 2020). We compared clinical course and outcomes based on the presence of troponin elevation and identified predictors of mortality. RESULTS: The cohort included 2716 COVID-19-positive admitted patients for whom troponin was drawn. Of these patients, 250 had troponin elevation (≥1.0 ng/mL). In the troponin-elevation arm, the minimum troponin level was 1.9 ± 8.82 ng/mL; maximum elevation was 10.23 ± 31.07 ng/mL. The cohort's mean age was 68.0 ± 15.0 years; 52.8% were men. Most (68.5%) COVID-19-positive patients with troponin elevation were African American. Patients with troponin elevation tended to be older, with more co-morbidities, and most required mechanical ventilation. In-hospital mortality was significantly higher (48.4%) in COVID-19-positive patients with concomitant troponin elevation than without troponin elevation (12.2%; p < 0.001). CONCLUSION: COVID-19 patients with troponin elevation are at higher risk for mechanical ventilation and mortality. Efforts should focus on early recognition, evaluation, and intensifying care of these patients.